A tool for empirical forecasting of major flares, coronal mass ejections, and solar particle events from a proxy of active-region free magnetic energy - Falconer, David; Barghouty, Abdulnasser F; Khazanov, Igor; Moore, Ron (Space Weather, 2011)
This paper describes a new forecasting tool developed for and currently being tested by NASA's Space Radiation Analysis Group (SRAG) at Johnson Space Center, which is responsible for the monitoring and forecasting of radiation exposure levels of astronauts. The new software tool is designed for the empirical forecasting of M- and X-class flares, coronal mass ejections, and solar energetic particle events. For each type of event, the algorithm is based on the empirical relationship between the event rate and a proxy of the active region's free magnetic energy. Each empirical relationship is determined from a data set of ~40,000 active-region magnetograms from ~1300 active regions observed by SOHO/Michelson Doppler Imager (MDI) that have known histories of flare, coronal mass ejection, and solar energetic particle event production. The new tool automatically extracts each strong-field magnetic area from an MDI full-disk magnetogram, identifies each as a NOAA active region, and measures the proxy of the active region's free magnetic energy from the extracted magnetogram. For each active region, the empirical relationship is then used to convert the free-magnetic-energy proxy into an expected event rate. The expected event rate in turn can be readily converted into the probability that the active region will produce such an event in a given forward time window. Descriptions of the data sets, algorithm, and software in addition to sample applications and a validation test are presented. Further development and transition of the new tool in anticipation of SDO/HMI are briefly discussed.